Soil genesis in Rio de las Vueltas valley, Santa Cruz province, Patagonia - Villegas, D.C. (2004)
Factors of soils formation, parent material, and relief in western part of Santa Cruz province (southermost Patagonia) were studied in rio de las Vueltas valley beetween Laguna del Desierto and Lago Viedma (49oS-49o30′S y a 73o W). There is great soil variability related to a strong north-west-south-east bioclimatic and geomorphic gradient. Soils were studied in a NW-SE transect, where three different sectors could be distinguished. The western area, including the Patagonian Andean Cordillera and piedmont is characterised by strong landscape variations due to glacial processes, colluvial, glacial, cineritc and glacifluvial parent materials, a udic-xeric regime and Nothofagus woodlands. The landscape of the eastern area is mainly of glacial-fluvioglacial, fluvial origin, with aeolian landforms, an and regime, grassland-shrub steppe and large flat structural plain landscape. Because of their different landscape-relief features and parent materials, both areas have different soils associations. The western area is characterized by a distrudepts, udivitrands/hapludands and haploxerolls sequence, meanwhile the eastern by an haplargides, torriortents and haplocalcides trends. In the western area, podzolisation features were recognized. In the north-western sector, Bs and E horizons were recognized, and low pH base saturation values, due to climatic conditions, indicate ongoing podzolization. Elsewhere in the south-eastern sector calcium carbonate from the surface, basic pH and total saturation are soils main features. © 2004 Asociación Geológica Argentina.